Motherhood: Making meaning: Kaplan, M M (1992) Mothers’ Image of Motherhood: Case studies of twelve mothers. London: Routledge. - Walker, Cherryl (PINS-Psychology in Society, 2026)
This is an interesting study that does not, however, deliver as much as it promises. Perhaps psychologists will make more of the theoretical discussion, the methodologies employed and the very detailed (yet somehow opaque) case studies themselves. As a sociologist/historian with a particular interest in gender relations, I found the study too limited to contribute much to an exploration of the meaning(s) of motherhood theoretically. The empirical findings, too, are interesting but slight, and ultimately of a negative rather than positive value. They prompt questions about the validity of other studies, notably Nancy Chodorow’s highly influential work, The reproduction of mothering (1978), but they do not lead the author to alternative theoretical claims or even hypotheses. After 200 pages, half of them describing her twelve case studies in great detail, Kaplan emphasises the value of "small-scale, systematic qualitative research" for "exploring and building theory" (p203), but then concedes two pages on, in her concluding paragraph: It would be difficult to know how to generalize from these twelve women to all mothers."